2017
DOI: 10.3892/or.2017.6130
|View full text |Cite|
|
Sign up to set email alerts
|

microRNA‑196b promotes cell migration and invasion by targeting FOXP2 in hepatocellular carcinoma

Abstract: Accumulating evidence indicates that microRNAs (miRNAs) play important roles in tumorigenesis and metastasis. Recent research has shown that miR‑196b is implicated in metastasis by regulating the migration and invasion of cancer cells. However, the clinical significance of miR‑196b and its role as well as the underlying mechanisms in hepatocellular carcinoma (HCC) remain largely unknown. Here, we detected miR‑196b expression in HCC and matched non-tumor tissues with qRT‑PCR. We found that miR‑196b displayed hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…Moreover, miR-196a was reported to contribute to cell proliferation through regulating cell cycle via targeting FOXO1 in HCC 23 . As for miR-196b, it was shown to predict poor prognosis and increase cell migration as well as invasion in HCC by regulating FOXP2 24 . Consistently with these reports, we also found that miR-196a and miR-196b knockdown could induce proliferation and apoptosis inhibition and indicate poor outcome of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, miR-196a was reported to contribute to cell proliferation through regulating cell cycle via targeting FOXO1 in HCC 23 . As for miR-196b, it was shown to predict poor prognosis and increase cell migration as well as invasion in HCC by regulating FOXP2 24 . Consistently with these reports, we also found that miR-196a and miR-196b knockdown could induce proliferation and apoptosis inhibition and indicate poor outcome of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Functional miRNAs are known to regulate targets expressions by binding their 3′-UTR sequences 26 . This research explored multiple targets of miR-196a and miR-196b and previous studies have validated the interaction between them and FOXO1, FOXP2, or lysosomeassociated protein transmembrane-4β (LAPTM4B) in HCC [22][23][24]27 . SOCS proteins mediate inflammation and apoptosis via regulating immune homeostasis in human cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous miRNAs are downregulated or upregulated in HCC, such as miR-21 (13), miR-493 (14), miR-873 (15) and miR-3662 (16). Upregulated miRNAs usually serve as oncogenes (17,18), whereas lowly expressed miRNAs display tumor-suppressor activity (19,20) in regards to HCC initiation and development. Therefore, inhibition or restoration of a specific miRNA might be an effective therapeutic technique for HCC treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, these authors also con rmed these results in vivo in a nude mouse model [17]. Furthermore, it should be noted that FOXP2 has also been associated with the promotion of migration and invasion of tumor cellsin breast cancer [26,27], hepatocellular carcinoma [14], prostate cancer [10] and colorectal carcinoma [28], among others. Therefore, results from in vitro studies suggest that FOXP2 may promote the malignant biological behavior of glioma cells.…”
Section: Foxp2 Expression In Glioblastomamentioning
confidence: 68%
“…On the one hand, high expression of FOXP2 has been associated with a bad prognosis in prostate cancer [10], neuroblastoma [11] and multiple mieloma [12]. On the other hand, other studies have reported an association between FOXP2 expression and a better prognosis in breast cancer [13], liver cell carcinoma [14], osteosarcoma [15] and gastric cancer [16]. Thus, whether FOXP2 is a tumor suppressor or tumor-promoting gene is matter of controversy.…”
Section: Introductionmentioning
confidence: 99%